Disease Burden of Group B Streptococcus Among Infants in Sub-Saharan Africa: A Systematic Literature Review and Meta-analysis. Issue 9 (September 2016) - Sinha, Anushua; Russell, Louise B.; Tomczyk, Sara; Verani, Jennifer R.; Schrag, Stephanie J.; Berkley, James A.; Mohammed, Musa; Sigauque, Betuel; Kim, Sun-Young
Abstract : Background: Group B streptococcus (GBS) is a leading neonatal sepsis pathogen globally. Investment in GBS disease prevention, such as maternal vaccination, requires evidence of disease burden, particularly in high infant mortality regions like sub-Saharan Africa. We aimed to provide such evidence by conducting a systematic literature review and meta-analysis to estimate maternal colonization proportion, GBS disease incidence and GBS serotype distribution. Methods: MEDLINE, MEDLINE in process and Cochrane Library were searched for studies published during 1990–2014, pertaining to sub-Saharan Africa. Eligible studies were used to estimate the proportion of pregnant women colonized with GBS, early-onset GBS disease incidence, late-onset GBS disease incidence and respective serotype distributions. Random effects meta-analysis was conducted to estimate weighted means and confidence intervals (CIs). Results: We identified 17 studies of colonization, 9 of disease incidence, and 6 of serotype distribution meeting inclusion criteria. 21.8% (95% CI: 18.3, 25.5) of expectant women were colonized with GBS. The incidence of early-onset GBS disease was 1.3 per 1000 births (95% CI: 0.81, 1.9), that of late-onset GBS disease 0.73 per 1000 births (95% CI: 0.48, 1.0). The most common disease-causing serotype was 3, followed by 1a. Serotypes 1b, 2 and 5 were next most common in frequency. Conclusion: Despite methodological factors leading to underestimation, GBS disease incidence appears high in sub-Saharan Africa. A small number of GBS serotypes cause almost all disease. GBS disease burden in sub-Saharan Africa suggests that safe, effective and affordable GBS disease prevention is needed.